Misdiagnosis of Leprosy with Severe Reversal Reaction as Psoriatic Arthritis: A Case Report and Literature Review - Gunawan H; Hidayah RMN; Ruchiatan K; Pangastuti M; Usman HA; Amalia F (Clinical, Cosmetic and Investigational Dermatology)
Hendra Gunawan,1 Risa Miliawati Nurul Hidayah,1 Kartika Ruchiatan,1 Miranti Pangastuti,1 Hermin Aminah Usman,2 Fatimah Amalia1 1Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran – Dr. Hasan Sadikin General Hospital, Bandung, West Java, Indonesia; 2Department of Pathological Anatomy, Faculty of Medicine, Universitas Padjadjaran – Dr. Hasan Sadikin General Hospital, Bandung, West Java, IndonesiaCorrespondence: Hendra Gunawan, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran – Dr. Hasan Sadikin General Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +6281221111215, Email h.gunawan2016@unpad.ac.idIntroduction: Leprosy is a chronic granulomatous disease caused by Mycobacterium leprae and Mycobacterium lepromatosis. Meanwhile, leprosy reactions are immunologically mediated episodes of acute or subacute inflammation that occur during the chronic course of the disease. Leprosy and leprosy reaction have a wide range of clinical manifestations, including those resembling psoriatic arthritis.Case Presentation: A 30-year-old male was consulted by a rheumatologist with psoriatic arthritis and psoriasis vulgaris. History of recurrent painfully swollen fingers and multiple erythematous plaques covered with thick scales in the last two years was discovered. A physical examination revealed edema on the eyelids and all fingers of both hands and feet, accompanied by painful interphalangeal joints. There were anesthetic and hypoestetic erythematous plaques covered by thick scales on both upper and lower extremities and epigastric region. Non-tender enlargements with a rubbery consistency were found on the right great auricular nerve and both common peroneal nerves. Slit-skin smear examinations from anesthetic lesions on the left arm showed bacterial index 3+, and skin biopsies from anesthetic lesions on the left thigh revealed a granulomatous reaction with epithelioid cells, Langhans giant cells, and lymphocyte infiltration. The patient was diagnosed as mid-borderline leprosy with severe reversal reaction, then received multidrug therapy–multibacillary and prednisone. The improvement of skin lesions and fingers edema were found on the 40th day of observation.Conclusion: The varying symptoms of leprosy can lead to misdiagnosis. Proper training for healthcare professionals is crucial to ensure timely and accurate treatment.Keywords: leprosy, misdiagnosed, psoriatic arthritis, reversal reaction, rheumatic